2022
DOI: 10.1002/cphc.202200069
|View full text |Cite
|
Sign up to set email alerts
|

DFT Study of the BH4 Hydrolysis on Au(111) Surface

Abstract: The mechanism of the catalytic hydrolysis of BH4− on Au(111) as studied by DFT is reported. The results are compared to the analogous process on Ag(111) that was recently reported. It is found that the borohydride species are adsorbed stronger on the Au0‐NP surface than on the Ag0‐NP surface. The electron affinity of the Au is larger than that of Ag. The results indicate that only two steps of hydrolysis are happening on the Au(111) surface and the reaction mechanism differs significantly from that on the Ag(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(31 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…S1, ESI† 35–37,59 ), that didn’t consider solvation effects, the hydrogen binding energies are higher than other published results. 13…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S1, ESI† 35–37,59 ), that didn’t consider solvation effects, the hydrogen binding energies are higher than other published results. 13…”
Section: Resultsmentioning
confidence: 99%
“…The hydrogen binding energies on the metal surfaces is compared with the previous studies and the values are in line with the reported values (Table S2, ESI† 31,34 ), though, they are higher than the reported values due to the differences in the computational methods used. 13…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations